2013 Picture Coding Symposium (PCS) 2013
DOI: 10.1109/pcs.2013.6737711
|View full text |Cite
|
Sign up to set email alerts
|

Sensor aided H.264 Video Encoder for UAV applications

Abstract: This paper presents a new low-complexity H.264 encoder for Unmanned Aerial Vehicles (UAV) applications. Standard video coding systems currently employed in UAV applications do not rely on some peculiarities in terms of scene 3D model and correlation among successive frames. In particular, the observed scene is static, i.e. the camera movement is dominant, and it can often be well approximated with a plane. Moreover, camera position and orientation can be obtained from the navigation system. Therefore, correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In this paper, as a natural continuations of the studies reported in (Angelino et al, 2012, Angelino et al, 2013b and (Angelino et al, 2013a), we propose a sensor aided video encoder to be used at high resolution and low frame rates on aerial video sequences. The proposed encoder is obtained modifying the open source implementation of h.264/AVC video coding standard (ISO/IEC, 2006) x264 (Merritt and Rahul, 2006) and fully compliant with h.264.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In this paper, as a natural continuations of the studies reported in (Angelino et al, 2012, Angelino et al, 2013b and (Angelino et al, 2013a), we propose a sensor aided video encoder to be used at high resolution and low frame rates on aerial video sequences. The proposed encoder is obtained modifying the open source implementation of h.264/AVC video coding standard (ISO/IEC, 2006) x264 (Merritt and Rahul, 2006) and fully compliant with h.264.…”
Section: Introductionmentioning
confidence: 76%
“…The Inter prediction is performed by a ME step, in witch the translational motion vector is estimated for every block of the video frame to encode, followed by a motion compensation process, in witch the block of the previously encoded (and decoded) video frame is translated on the current block position. In (Angelino et al, 2013b) the authors propose to modify a well known open source implementation of a standard h.264 encoder, x264, which uses the metadata provided by the navigation system of the UAV in order to accurately predict the MVs, at low frame rates also. Experimental results showed that in such way both better quality vs bitrate tradeoffs and lower computational complexity can be reached.…”
Section: Encoding Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Bhaskaranand et al [37] designed a video encoding scheme suitable for applications in which encoder complexity needs to be low (e.g., UAV video surveillance). Encountering the same problem, Angelino et al proposed a novel motion estimation scheme that employs the global motion information provided by the onboard navigation system [38,39]. The homography between two images was utilized to initialize the block matching algorithm, allowing for a more robust motion estimation and a smaller search window to reduce complexity.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, all pixels of an image are assumed to be on the same plane. Field depth consistency is a basic hypothesis in most studies on GME [35][36][37][38][39]. The lower the terrain fluctuations and buildings are, the more accurate the result of GME is.…”
Section: Study Hypothesesmentioning
confidence: 99%